A Tick Vector Transmission Model of Monocytotropic Ehrlichiosis - Saito, Tais Berelli (J Infect Dis, 2015)
Background. Ehrlichioses are emerging, tick-borne diseases distributed worldwide. Previously established animal models use needle inoculation as a mode of infection; however, there is limited representation of natural transmission in artificially inoculated models compared with transmission by the tick vector. The objective of this study was to develop a tick vector transmission animal model of ehrlichial infection using a human pathogen, Ehrlichia muris–like agent (EMLA). Methods. Ixodes scapularis larvae were fed on EMLA-infected mice, and after molting, infected nymphs were used to infest naive animals. Results. Ehrlichiae were acquired by 90%–100% of feeding larvae. The majority of animals fed upon by infected nymphs developed sublethal infection with 27% lethality. Bacteria disseminated to all tissues tested with greatest bacterial loads in lungs, but also spleen, lymph nodes, liver, kidneys, brain, and bone marrow. Numerous foci of cellular infiltration, mitoses, and hepatocellular death were observed in liver. Mice infected by tick transmission developed higher antiehrlichial antibody levels than needle-inoculated animals. Tick-feeding-site reactions were observed, but there was no observed difference between animals infested with infected or uninfected ticks. Conclusions. For the first time we were able to develop a tick transmission model with an Ehrlichia that is pathogenic for humans.